A local geoid in Dronning Maud Land - Eiken, Trond; Omang, Ove Christian Dahl; Øvstedal, Ola (24th General Assembly European Geophysical Society, 1999)
The main purpose of the present paper is to estimate the orthometric height of the GPS-station at Troll, Dronning Maud Land, Antarctica. Located at approximately 1300 m Troll has been connected to the GIANT-network, but it's orthometric height remains undetermined. A local geoid has been determined based on available gravity anomalies and vertical angle mesurements. Information about the ice-thickness has been included in the terrain model. Based on tidal measurements the mean sea level was determined in Jutulgryta, a rift zone in the Fimbulisen ice shelf. Several gravity- and GPS-stations were measured between the two points (Jutulgryta and Troll), a distance of approximately 100 km.
Keywords: Dronning Maud Land; NARE ekspedisjoner; Troll forskningsstasjon; geodesi; kartlegging

Accumulation of heavy metals in an Antarctic food-chain - Lie, Elisabeth; Steinnes, Eiliv ("Heavy metals in the environment", 10th International Conference, 1995)
Keywords: Antarktis; forurensning; miljøgifter; næringskjede

Environmental radioactivity in the Arctic and Antarctic - Holm, Elis (red.); Strand, Per (red.) ("International Conference on Environmental Radioactivity in the Artic and Antarctic organized by Norwegian Radiation Protection Authority, Norway and Department of Radiation Physics, Lund University, Sweden., 1993)
Keywords: Antarktis; miljøforurensing; polarområdene; radioaktivitet

Petrology of volcanic rocks in the Bouvet Island (Bouvetøya), South Atlantic - Prestvik, Tore; Goles, Gordon; Basu, Asish R (Geological Society of America, Annual Meeting, 1993)
Keywords: Bouvetøya; geologi; petrologi